Clinical Outcome of a Portosplenomesenteric Venous Thrombosis in Necrotizing Acute Pancreatitis with Protein C and S Deficiency Treated by Anticoagulation Therapy Alone - Firmin Ankouane; Mathurin Kowo; Bernadette Ngo Nonga; Eric Magny; Edith Hell Medjo; Elie Claude Ndjitoyap Ndam (Case Reports in Gastrointestinal Medicine)
Cases of splanchnic venous thrombosis have not been described in Cameroon. Their prevalence in acute pancreatitis is variable. With the emergence of acute intra-abdominal infections including typhoid fever and peritoneal tuberculosis in situations of acquired immunodeficiency syndrome, these cases will become frequent. We report the case of a portosplenomesenteric venous thrombosis related to necrotizing acute pancreatitis associated with proteins C and S deficiency, in a 46-year-old Cameroonian man, without particular past medical history. He was admitted for abdominal pain which had been evolving for 3 weeks and accompanied by vomiting. In the absence of hemorrhagic risk factor, the patient received low molecular weight heparin followed by oral warfarin. The abdominal ultrasound check on the 12th day showed a partial recanalization of venous thrombosis. The abdominal contrast-enhanced CT scanner at day 30 on oral anticoagulation therapy showed collateral vessels and small bowel edema. At the same time the upper gastrointestinal endoscopy showed grade II esophageal varices. We have maintained oral anticoagulation therapy. This case highlights that an early effective anticoagulation heparin therapy is needed for a clear benefit in case of suspected PSMVT. It is certain that the sooner the treatment is given, the better outcome will be.